Chemical Extraction of the Available Iron Present in Soils - CELIK, HAKAN; VAHAP KATKAT, ALI (Asian Journal of Chemistry, 2010)
The available iron contents of 40 different soils were determined by using 10 different chemical extraction methods. Maize plants were grown at greenhouse conditions to compare the most appropriate method. Dry matter yields (g pot-1), total and active iron contents of the plants (mg Fe kg-1), total and active iron amounts taken from the soils (mg pot-1) of non-applied iron pots and their relative amounts (Fe0/Fe3 × 100) were used as biological indices. The available iron amounts of the soils found different according to the chemical extraction methods. 0.05 M EDTA (pH 7), 0.005 M diethylene triamine pentaacetic acid (DTPA) + 0.01 M CaCl2 + 0.1 M triethanolamine (TEA) (pH 7) and active Fe(COONH4)2. H2O + (COOH)2.2H2O methods used for predicting available iron content of the soils gave a high degree of correlation with the biological indices. However, because of giving much more correlations with the biological indices, 0.05 M EDTA (pH 7) method suggested as the best determination method for assessing availability of iron in these soils.